2022
DOI: 10.1039/d1sc04832e
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning the spike: role of the nature and topology of the glycan shield in the structure and dynamics of the SARS-CoV-2 S

Abstract: The dense glycan shield is an essential feature of the SARS-CoV-2 spike (S) architecture, key to immune evasion and to the activation of the prefusion conformation. Recent studies indicate that...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 54 publications
3
107
0
Order By: Relevance
“… 27 Fadda elaborates this site has high affinity for neutral or negatively charged oligosaccharides. 34 Additionally, Casalino et al’s simulations illustrate that the RBM is one of the most flexible regions in the spike head, second only to the furin cleavage site ( Figure S2 ). 15 The RBM’s/site B’s conformational diversity is exemplified clearly in Figure 3 C. Despite drastic differences in protein and glycan topography around the RBM, site B is highly populated in all four protein conformations for all GAG models ( Table S3–7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 Fadda elaborates this site has high affinity for neutral or negatively charged oligosaccharides. 34 Additionally, Casalino et al’s simulations illustrate that the RBM is one of the most flexible regions in the spike head, second only to the furin cleavage site ( Figure S2 ). 15 The RBM’s/site B’s conformational diversity is exemplified clearly in Figure 3 C. Despite drastic differences in protein and glycan topography around the RBM, site B is highly populated in all four protein conformations for all GAG models ( Table S3–7 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the remaining 14 surface binding sites, we identified 6 novel binding sites (F, G, K, L, M, N) and validated 8 previously identified binding sites (A, B, C, D, E, H, I, P) ( Figure S8 ). Sites C, B, and D correspond to a “supersite” formed between the RBD patch 23 , 27 and RBD cleft 34 sites (C, B, and D are analogous sites centered on one of each spike protomers), sites E and H correspond to the connecting ridge posited by Wade and co-workers 35 which connects the RBD supersite down to the furin-cleavage site, site I is similar to the NTD site proposed by Gandhi and co-workers. 36 Our results support the importance of these sites for GAG binding and reaffirm the need to focus on these regions when studying the role of HS in SARS-CoV-2 host-cell invasion mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many different key functions driving the evolution of the shield, glycans can be aiding S folding and structural integrity [ 33 , 41 ], facilitate the interaction with cellular factors [ 42 , 43 ], or be shielding underlying epitopes [ 33 , 44 ]. Because of this key functional role, the glycan shield evolved significantly along the phylogeny, and it is continually evolving [ 45 ], with the very recent loss of N370 glycosylation due to T372A mutation in SARS-CoV-2. Through molecular dynamics (MD) simulation, it has been observed that presence of both N234 and N370 results in tying the closed RBDs together, and likely hinders the RBD opening [ 45 , 46 , 47 ].…”
Section: Role Of Glycans In Protein Folding and Stabilitymentioning
confidence: 99%
“…Because of this key functional role, the glycan shield evolved significantly along the phylogeny, and it is continually evolving [ 45 ], with the very recent loss of N370 glycosylation due to T372A mutation in SARS-CoV-2. Through molecular dynamics (MD) simulation, it has been observed that presence of both N234 and N370 results in tying the closed RBDs together, and likely hinders the RBD opening [ 45 , 46 , 47 ]. This possibly explains the absence of N370 glycan site in SARS-CoV-2.…”
Section: Role Of Glycans In Protein Folding and Stabilitymentioning
confidence: 99%